Gastrointestinal and hepatic diseases during the COVID-19 pandemic: Manifestations, mechanism and management - Mohamed, Dina Zakaria (World J Gastroenterol, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is considered the causative pathogen of coronavirus disease 2019 (COVID-19) and has become an international danger to human health. Although respiratory transmission and symptoms are still the essential manifestations of COVID-19, the digestive system could be an unconventional or supplementary route for COVID-19 to be transmitted and manifested, most likely due to the presence of angiotensin-converting enzyme 2 (ACE2) in the gastrointestinal tract. In addition, SARS-CoV-2 can trigger hepatic injury via direct binding to the ACE2 receptor in cholangiocytes, antibody-dependent enhancement of infection, systemic inflammatory response syndrome, inflammatory cytokine storms, ischemia/reperfusion injury, and adverse events of treatment drugs. Gastrointestinal symptoms, including anorexia, nausea, vomiting, and diarrhea, which are unusual in patients with COVID-19, and some digestive signs may occur without other respiratory symptoms. Furthermore, SARS-CoV-2 can be found in infected patients’ stool, demonstrating the likelihood of transmission through the fecal-oral route. In addition, liver function should be monitored during COVID-19, particularly in more severe cases. This review summarizes the evidence for extra-pulmonary manifestations, mechanisms, and management of COVID-19, particularly those related to the gastrointestinal tract and liver.